RELATIONSHIP BETWEEN 25-HYDROXYVITAMIN D BLOOD LEVELS AND MICROALBUMINURIA IN TYPE 2 DIABETES (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the prevalence of 25-Hydroxyvitamin D blood deficiency and analyze theassociation between 25-Hydroxyvitamin D with microalbumin in patients with type 2 diabetes.Subjects and methods: A descriptive cross-sectional study on 90 patients were diagnosed with type2 diabetes at the Department of Nephrology – Endocrinology, Da Nang Hospital.Results: The percentage of blood 25-Hydroxyvitamin D deficiency in patients with type 2 diabeteswas 20%. 25-Hydroxyvitamin D blood levels were negatively correlated with the degree ofalbuminuria (r = -0,216; p < 0,05).
Keywords: 25-Hydroxyvitamin D, diabetes, albuminuria.